A Conversation About the Ethics of Past and Future Memory Care Models: Perspectives from the First Two European Dementia Villages - Emily Roberts Ph.D (SAGE Publishing, 2023)
Dementia care organizations face a range of daunting environmental changes and challenges. Internationally, there is a long history of efforts to improve quality of care and life for individuals with dementia. In a time of particular attention to the images of older adults confined to a single or shared room in a care facility due to COVID-19, autonomy becomes the overarching problem, not only because in general institutions limit the freedom of frail elders, but because the existential conditions that create the need for long term care such as chronic disease, cognitive decline, and the need for general support with activities of daily living (ADLs) rail against the autonomy of independent self-sufficiency. Additionally, these environments are institutional in design and size, with little access to outdoor spaces and other amenities. This perspective manuscript addresses the ethics of past and future memory care models, looking specifically at the European Dementia Village (DV) model. This model allows for autonomy and continuation of patterns of daily living through housing integrated with exterior walks, gardens, restaurants, and amenities within familiar and normal surroundings. This pioneering health care experiment negotiates rivaling discourses of intimacy, professionalization, and medicalization. In order to get a deeper understanding of the culture and ethics of this integrated care model, the first two dementia village sites were visited which included meetings with care staff and administrators. Those conversations and observations led to a series of aligned themes relating to the ethics of the DV model which include: the strength of the social approach, clinical support, resident/staff collaborations, and advocating for ethical dementia care. Rethinking the ethics of dementia care entails individual perspectives and group discussions on what can keep individuals social connected within their care community, including focusing on strengths of the individual and normalized daily routines.